Pemanfaatan Teknologi Informasi dan Komunikasi dalam Pembelajaran di SMP Bustanul Makmur Genteng Banyuwangi: Utilization of Information and Communication Technology in Learning at Bustanul Makmur Junior High School Genteng Banyuwangi - Mundir Mundir (Fenomena, 2010)
This case study aims at exploring the use of information and communication technology (ICT) in teaching and learning process at Bustanul Makmur Junior High School Genteng Banyuwangi. Specifically, the research focuses on (1) the profile of Bustanul Makmur Junior High School, (2) the realization of the use of ICT in teaching and learning process at Bustanul Makmur Junior High School, (3) background or the motivation behind the use of ICT in teaching and learning process, (4) teachers’ and students’ responses toward the use of ICT in teaching and learning process, and (5) supporting factors and obstacles to the use of ICT in teaching and learning process. Studi kasus ini bertujuan untuk mengeksplorasi penggunaan teknologi informasi dan komunikasi (TIK) dalam proses pembelajaran di SMP Bustanul Makmur Genteng Banyuwangi. Secara khusus, penelitian ini berfokus pada (1) profil SMP Bustanul Makmur, (2) realisasi penggunaan TIK dalam proses pembelajaran di SMP Bustanul Makmur, (3) latar belakang atau motivasi di balik penggunaan TIK dalam proses pembelajaran, (4) tanggapan guru dan siswa terhadap penggunaan TIK dalam proses pembelajaran, dan (5) faktor pendukung dan penghambat penggunaan TIK dalam proses pembelajaran.